2009
DOI: 10.1007/s11663-009-9328-x
|View full text |Cite
|
Sign up to set email alerts
|

Leaching of Chalcopyrite with Sodium Hypochlorite

Abstract: A laboratory study was conducted on the leaching of chalcopyrite with NaOCl (sodium hypochlorite). Experiments were carried out in the following two stages: (1) Chalcopyrite was converted to CuO (cupric oxide) with a sodium hypochlorite solution, and (2) cupric oxide was dissolved to cupric ions with 1 normal sulfuric acid at room temperature. In the first-stage leaching, the initial pH varied from 12.5 to 13.7, the temperature from 35°C to 75°C, the sodium hypochlorite concentration from 0.2 to 0.85 molar, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 7 publications
(7 reference statements)
1
7
0
Order By: Relevance
“…The leach activation energy, in the absence of the initial addition of Fe 3+ , was found to be 80 ± 10 kJ mol À1 and 84 ± 10 kJ mol À1 for Cu and Fe, respectively, suggesting that the leaching process is chemical reaction controlled, which is in general agreement with the rate limiting step reported by Al-Harasheh et al (2005) and Garlapalli et al (2010).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The leach activation energy, in the absence of the initial addition of Fe 3+ , was found to be 80 ± 10 kJ mol À1 and 84 ± 10 kJ mol À1 for Cu and Fe, respectively, suggesting that the leaching process is chemical reaction controlled, which is in general agreement with the rate limiting step reported by Al-Harasheh et al (2005) and Garlapalli et al (2010).…”
Section: Discussionsupporting
confidence: 89%
“…The rate of chalcopyrite dissolution is increased in the presence of strong and/or high concentrations of oxidants (Palmer et al, 1981;Lin et al, 1986;Antonijevic et al, 2004;Aydogan et al, 2006;Garlapalli et al, 2010) and at high temperatures (Hackl et al, 1995;Al-Harahsheh et al, 2008;Sokic et al, 2009). It is clear that temperature is one of the key factors that directly affects chalcopyrite dissolution kinetics with a considerable number of studies having been reported (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Equation ( 4) is the predominant reaction in acidic solutions with elemental sulfur as the main product while thiosulfate (reaction similar to (5)) has been proposed as occurring in ammoniacal solutions (pH 9 to 10) (Moyo et al, 2015). The formation of sulfate (equation 6) has been observed and used for analysis of leach data in alkaline (pH 12 to 13) solutions containing hypochlorite (Garlapalli et al, 2010) and is therefore most likely in strongly alkaline solutions. Other iron oxides such as FeO and Fe 3 O 4 are also possible products and reaction (7) has been written in terms of the former.…”
Section: Thermodynamicsmentioning
confidence: 99%
“…(Velásquez-Yévenes et al, 2010, 2010a, 2010bNicol, 2018;Moyo et al, 2018Moyo et al, , 2019 but only chloride has been applied in heap leach practice (Velásquez-Yévenes et al, 2010). Following a paper some years ago (Garlapalli et al, 2010) on the oxidation of chalcopyrite in sodium hydroxide solutions by hypochlorite, a recent paper on the same topic (Choubey, 2018) has renewed interest in a possible two-step process in which oxidation in alkaline solutions is followed by dilute acid leaching of the oxidation residue to selectively leach the copper. However, these publications did not address the fundamental aspects of the alkaline oxidation of chalcopyrite that is the focus of this study.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13] Various other oxidizing agents were investigated as well, such as hydrogen peroxide, ammonium persulfate, hypochlorite and ozone. [14][15][16][17] All these studied processes can leach copper to some extent, but there are some disadvantages. In sulfate media, the leaching kinetics are generally slow (several months) and the leaching of copper is difficult to be complete, due to the formation of passivation layers on the surface of chalcopyrite, such as solid sulfur and iron precipitate (e.g.…”
Section: Introductionmentioning
confidence: 99%